The Effect Of Corporate Governance On The Integrity Of Financial Reports In Transportation And Logistic Companies - Frida Eka Ristanti; Agus Eko Sujianto; Kutbuddin Aibak (Economics and Digital Business Review, 2025)
This study aims to analyze the influence of corporate governance, including institutional ownership, managerial ownership, and independent commissioners, on the integrity of financial statements in transportation and logistics companies. The integrity of financial statements is an important aspect in maintaining stakeholder trust because it reflects the reliability and honesty of financial information presented by the company. This study uses a quantitative method with secondary data obtained from the annual financial statements of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2020 period. The results show that managerial ownership and independent commissioners have a positive effect on the integrity of financial statements, while institutional ownership has no effect on the integrity of financial statements. These findings indicate that corporate governance mechanisms, particularly oversight by managerial investors and the role of independent commissioners, can improve the quality and integrity of a company's financial statements. This research is expected to contribute to the development of accounting literature and become a consideration for management and investors in decision-making.